UPACARA â€œTOLAK BALAâ€ REFLEKSI KEARIFAN LOKAL MASYARAKAT NELAYAN KENAGARIAN PAINAN KABUPATEN PESISIR SELATAN PROPINSI SUMATERA BARAT TERHADAP LAUT - Fitrisia, Azmi (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2014)
Nagari (local village) of Painan is a fishing area located in Pesisir Selatan Regency, West Sumatera Province. Sometimes the number of fish fished in this area is so low. The community believes the reason for this is some kind of mystical strength. Therefore they try to avoid it by holding ‘tolak bala’ (rejecting misfortune) ceremony. The main question of this study is what role does the ceremony play in the Painan fishermen community? The data is analysed using functional structural theory of Redcliffe-Brown. As a materialization of local wisdom, the ceremony is important among the fishermen community. Religious, social, and economic aspects of the ceremony can change the perception of society. Fishermen realize the harmony between human and supernatural creatures. In the other hand, the ceremony helps develop and preserve the social binding and teach them about the importance of saving and economical spending.Keywords: ‘tolak bala’, local wisdom, fishermen